Digestibilidade e exigência de aminoácidos para rã-touro - Mansano, Cleber Fernando Menegasso [UNESP] (2015)
The national raniculture requires the development of diets that meets the needs of those animals economically and to decrease the amount of organic matter and phosphorus in aquatic environment in a sustainable manner. Two experiments were conducted to determine the protein, energy, lipids and amino acid digestibility of the ingredients used to prepare diets for bullfrogs in three different stages of development, through the ideal protein concept, estimate the requirement of digestible amino acids and verify the effects of lysine supplementation in diets for bullfrogs. There were differences in digestibility of the ingredients and differences between the development animal stages. The animals used efficiently the protein and energy fractions of the salmon by-product meal and corn gluten. The animals used the lipid fraction of the salmon by-product meal, poultry by-product meal, sardines by-product meal, soy protein concentrate, and wheat bran and soybean oil efficiently. These feedstuffs are recommended in the bullfrog's diets. The protein feedstuffs of animal origin that showed the highest apparent digestibility coefficients of the essential aminoacids, for initial, growing and finishing were poultry by-product meal, salmon by-product meal and blood meal spray dried, respectively. The apparent digestibility coefficients for essential amino acids for protein feedstuffs of plant origin (soy protein concentrate, soybean meal and corn gluten), were higher than the apparent digestibility coefficients for essential amino acids for energetic feedstuffs of plant origin (corn grain and wheat bran). The determination of the best values for the evaluated parameters in function of the minimum required level of lysine were performed using the LRP (Linear Response Plateau). The digestible lysine requirement for bullfrogs is 1.82% of the diet or 6.55% of digestible protein, providing more protein retention efficiency